A Pragmatic Analysis Of The Pedagogical Implications Of The Use Of English Epistemic Modality Written Literary Discourse - Lalu Muhaimi; Sribagus Sribagus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2019)
Abstract : This is a pragmatic study of the use of the items of epistemic modality in a literary discourse with the main aims to identify, analyze and describe the ways the items of epistemic modality are used. Their contextual meanings, functions, and implication to the pedagogical attempts are also unfolded. The results of the interpretative and descriptive analysis reveal that the items of epistemic modality are found to be very dominant which also suggests that the genre of narrative fiction is linguistically characterized by the utterances that are established on the basis of knowledge and reasoning. The items of epistemic modality are found to be polysemous and polyfunctional which are reflected pragmatically in the forms of politeness, negotiative and constructive functions. All these lead to the acknowledgement that the use of the items of linguistic modality in literary discourse and their usage for language teaching in the applied linguistic contexts is worth conducting.Keywords: pragmatics, Linguistic modality, Epistemic modality, Pedagocical implication